Mbailundu Remembered: Colonial Traces in Post-Civil War Angola - Melnysyn, Shana (Kronos: Southern African Histories, 2018)
This article traces connections between structures, identities and forms of collective belonging that impacted social relations in Angola from roughly the 1880s to 2013. In the absence of a coherent, centralised state structure, both during Portuguese colonialism and after independence in 1975, communities coalesced around regional and ethnic identities that had begun hardening under colonial rule. These structures of conflict and inequality animated the Angolan civil war (1975–2002). Through the lens of oral histories and collective memories of the early twentieth century, as well as archival records, I show how Angola’s exclusionary identity politics were forged during colonial times and have persisted into the 21st century. Focusing on the Umbundu speaking kingdom of Mbailundu, in Angola’s central highlands, this article suggests that colonial structures of belonging and exclusion continue to affect political life in 21st century Angola by maintaining stark divisions between people of different regional, ethnic and religious backgrounds. A fractured picture of belonging and loyalty emerged out of settler colonial structures in Angola and continues to reverberate in the political intrigues that overshadow everyday life.